Safranin dye degradation by using Fe2O3-SnO2 Nanocomposites under natural Sunlight - PANDIT, Vikram Rama Uttam (Biopolymer Applications Journal, 2025)
Metal oxide based semiconductor photocatalysts are well known for multifunctional applications. Herein, we have reported the ex-situ synthesis of Fe2O3-SnO2 nanocomposite system using simple wet impregnation method. Total five semiconductor nanomaterial photocatalysts were prepared as Fe2O3, SnO2, 1, 2.5 and 5% of SnO2 over Fe2O3 surface. After successful synthesis of these photocatalysts its formation is checked using UV- Vis spectroscopy, FTIR and RAMAN analysis. Photocatalytic dye degradation performance is checked towards safranin dye using all the five photocatalyst systems. Resultant composite photocatalysts were not showed some impressive photocatalytic activities as compared to individuals. This above observation is may be due to the less gap between conduction band levels of both photocatalyst systems.